Indian Christianity and its public role : socio-theological explorations - Patrick, Gnana; University of Madras. Department of Christian Studies (Chennai : Department of Christian Studies, University of Madras & Christian World Imprints, New Delhi, 2019)
Contributed articles presented at a national consultation organized at University of Madras, Department of Christian Studies in February 2018.
Includes bibliographical references and index.
Keywords: Church and social problems -- India -- Congresses; Public theology -- India -- Congresses; Church work -- India -- Congresses